Implementasi Virtual Reality Berbasis Foto 360o Untuk Memvisualisasikan Fasilitas Perguruan Tinggi Surabaya - Nadiah Ratnaduhita; Ian Mahendra Putra; Ully Asfari; Yupit Sudianto; Benazir Imam Arif Muttaqin (Ikatan Ahli Informatika Indonesia (IAII), 2021)
The college selection process is an important phase because this process affects the future achievement targets of prospective students. One of the factors that is considered in determining a university is the supporting facilities provided during the lecture process. prospective students will continue to search and at the same time consider universities despite the pandemic COVID-19. By implementing 3600 photo-based virtual reality (VR), prospective students or external parties can get information about university facilities anytime and anywhere because it can be accessed online. This study uses the Multimedia Development Life Cycle (MDLC) method in application development, then uses a quantitative approach to test the feasibility of the application. The results showed that 3600 photo-based virtual reality (VR) is an alternative media in conveying information related to the facilities and logistics owned by universities, the variables of smoothness and convenience of operating 3600 photo-based videos have a high enough influence, but on user motivation to use VR is worth less. This happens because users are not used to using this technology.